PERSONHOOD AND CREATION IN AN AGE OF ROBOTS AND AI: CAN WE SAY "YOU" TO ARTIFACTS?: with Gillian K. Straine, "Artificial Intelligence and Robotics: Contributions from the Science and Religion Forum"; Michael S. Burdett, "Personhood and Creation in an Age of Robots and AI: Can We Say "You" to Artifacts?"; Mohammad Yaqub Chaudhary, "The Artificialization of Mind and World"; and David Hipple, "Encounters with Emergent Deities: Artificial Intelligence in Science Fiction Narrative." - Burdett, Michael S. (Zygon: Journal of Religion & Science, 2020)
This article explores the extent to which the I‐You relation should be applied to domains other than the human and the divine focusing particularly on artifacts and technology. Drawing first on the work of Martin Buber, Gabriel Marcel, and Martin Heidegger, I contend that the I‐You tradition has maintained I‐You relations with objects are possible even when these same figures level strong critiques of the I‐It relation. I extend these discussions and argue that some kind of You‐speaking for artifacts is needed to combat rampant consumption and reduction of the world to pure utility. But, I equally suggest that there are limitations to applying the I‐You relation to artifacts precisely when doing so keeps us from having genuine relationships with other people as outlined by psychologist Sherry Turkle. Finally, I outline how this proposal impacts the doctrine of creation. In sum, it expands our intuitions of what is included in that doctrine creation.